THE APPROVAL OF FREEHOLD TITLE IN INHERITANCE LAWSUIT AT GORONTALO RELIGIOUS COURT - Titin Samsudin; Nur Hairat Adam (Al-Bayyinah, 2020)
Freehold Title acts as strong evidence of that certificate holder, as long as there is no other more reliable evidence. In Case Number. 0337/Pdt.G/2016/PA.Gtlo. authentic freehold title is declared not legally binding while in Case Number 38/Pdt.G/2012/PN.Gtlo., quite the opposite. This research is library research, with an empirical juridical approach. This study focuses on the verdict of the Gorontalo Religious Court in Case Number 0337/Pdt.G/2016/PA.Gtlo. The findings of this study are that the Gorontalo District Judicial Judge’s verdict does not make the Gorontalo District Court decision as the basis. The panel of judges in the Verdict Number 0337/Pdt.G/2016/PA.Gtlo. emphasized more on the normative aspects in basing its verdict. The judge did not make a contextual approach in examining the condition of the defendant as an adopted child. The focus of the panel of judges is only on the procedure of making an authentic deed (grant deed), which is considered to be legally flawed and not legally binding. The courtesy of the judge in basing his consideration of the period of the plaintiff’s claim filing, the excellent relationship of the defendant (adopted child) with the heir. The research findings imply that the distribution of inheritance should be carried out properly. The process of claiming inheritance in the Religious Courts of the panel of judges must continue to consider the duration of this new inheritance so that the trial process is not complicated to solve.Keywords: Approval, Freehold Title, Inheritance.